2022
DOI: 10.1128/spectrum.00860-22
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Sensitivity of Saliva GeneXpert MTB/RIF Ultra for Tuberculosis Diagnosis in Adults in Uganda

Abstract: Tuberculosis is among the leading causes of morbidity and mortality worldwide, in large part because >3 million people go undiagnosed and untreated each year. Sputum has been the mainstay for TB diagnosis for over a century but can be difficult for patients to produce.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…From included manuscripts (appendix pp 26–33 for study characteristics; appendix p 5 includes full methodological details and results by study), we classified types of upper respiratory tract sampling into four groups: laryngeal swabs (32 studies 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ), nasopharyngeal aspirate (ten studies 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ), oral swabs (18 studies 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ), and other (mouthwash three studies, 71 , 72 , 73 nasal swabs one study, 74 saliva four studies, 75 , 76 , 77 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From included manuscripts (appendix pp 26–33 for study characteristics; appendix p 5 includes full methodological details and results by study), we classified types of upper respiratory tract sampling into four groups: laryngeal swabs (32 studies 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ), nasopharyngeal aspirate (ten studies 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ), oral swabs (18 studies 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ), and other (mouthwash three studies, 71 , 72 , 73 nasal swabs one study, 74 saliva four studies, 75 , 76 , 77 ,…”
Section: Resultsmentioning
confidence: 99%
“…From included manuscripts (appendix pp 26-33 for study characteristics; appendix p 5 includes full methodological details and results by study), we classified types of upper respiratory tract sampling into four groups: laryngeal swabs (32 studies ), nasopharyngeal aspirate (ten studies [43][44][45][46][47][48][49][50][51][52] ), oral swabs (18 studies [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] ), and other (mouthwash three studies, [71][72][73] nasal swabs one study, 74 saliva four studies, [75][76][77][78] and other mucosa or dental samples three studies [79][80][81] ). Studies were published between May 13, 1933, and Dec 19, 2022, from South Africa (11 studies), Norway (seven studies), UK (seven studies), Peru (four studies), Uganda (seven studies), Canada (three studies), India (three studies), USA (three studies), Australia (two studies), Germany (two studies), Kenya (two studies), and one study from each of Brazil, Chile, China, Slovakia and Czech Republic, Denmark, Finland, France, Hungary, Italy, Japan, Malawi, Moldova, Mozambique, South Korea, southeast Asia (individual countries not specified), Spain, Sweden, Taiwan, Turkey, and Yemen.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this is a rapidly developing field, and a modified search update identified additional evidence published or submitted since the full search was completed on Aug 23, 2023. Although no additional studies using swabs have been published, additional studies 28 have continued to explore saliva with findings of good sensitivity comparable with the highest sensitivities seen with oral swabs.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report by Shenai and coresearchers, the X-Classic showed a lower sensitivity in detecting MTB from saliva specimens compared with testing on sputum samples isolated from the same patients [ 21 ]. However, a recent study conducted in Uganda revealed that X-Ultra on a single saliva sample produced a sensitivity of 90% relative to the composite MGIT reference standard [ 22 ]. The use of X-Ultra and enrollment of only individuals with definite TB may explain the promising sensitivity of X-Ultra on saliva specimens in the latter study.…”
Section: Discussionmentioning
confidence: 99%